Response to the letter regarding article, “The impact of renin-angiotensin system inhibitors on colorectal neoplasm development” - Han, Yoo Min; Choi, Ji Min; Rhee, Tae-Min; Choi, Su-Yeon; Lee, Heesun (Clinical hypertension, 2025)
KCI Citation Count: 0